Pivotal role reelin signaling pathway in the development of tolerance to morphine-induced antinociception - Bambang Subakti Zulkarnanin; Junaidi Khotib (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
The huge endogenous macromolecule protein responsible for controlling migration and dendritic growth of developing neurons, reelin, has recently been proposed that its signaling pathway modulates synaptic plasticity in the adult rodent brain. This study was carried out to investigate the pivotal role of the reelin signaling pathway in the development of tolerance to morphine induced antinociception. There was evidence that repeated intracerebroventricular administration of reelin’s monoclonal antibody, the competitive inhibitor to reelin – apolipoprotein receptor E2 recombinant, and disabled1 (Dab1) protein inhibitor – MG132, resulted in the inhibition to the development of antinociception tolerance to morphine administration. Furthermore, chronic in vivo administration with morphine caused significance increase of the immunoreactivity (IR) for phosphorylated-Dab1 in the thalamus. These data suggested that persistent activation of reelin signaling pathway due to chronic administration of morphine may be responsible for the development of tolerance to morphine-induced antinociception.Key words: Morphine tolerance, Neuronal plasticity, Opioid receptor, Reelin signalling pathway